A novel difficulty scoring system for laparoscopic liver resection. (October 2014) - Ban, Daisuke; Tanabe, Minoru; Ito, Hiromitsu; Otsuka, Yuichiro; Nitta, Hiroyuki; Abe, Yuta; Hasegawa, Yasushi; Katagiri, Toshio; Takagi, Chisato; Itano, Osamu; Kaneko, Hironori; Wakabayashi, Go
Abstract Early on, laparoscopic liver resection (LLR) was limited to partial resection, but major LLR is no longer rare. A difficulty scoring system is required to guide surgeons in advancing from simple to highly technical laparoscopic resections. Subjects were 90 patients who had undergone pure LLR at three medical institutions (30 patients/institution) from January 2011 to April 2014. Surgical difficulty was assessed by the operator using an index of 1–10 with the following divisions: 1–3 low difficulty, 4–6 intermediate difficulty, and 7–10 high difficulty. Weighted kappa statistic was used to calculate the concordance between the operators' and reviewers' (expert surgeon) difficulty index. Inter‐rater agreement (weighted kappa statistic) between the operators' and reviewers' assessments was 0.89 with the three‐level difficulty index and 0.80 with the 10‐level difficulty index. A 10‐level difficulty index by linear modeling based on clinical information revealed a weighted kappa statistic of 0.72 and that scored by the extent of liver resection, tumor location, tumor size, liver function, and tumor proximity to major vessels revealed a weighted kappa statistic of 0.68. We proposed a new scoring system to predict difficulty of various LLRs preoperatively. The calculated score well reflected difficulty.